ANMP ad hoc network management protocol. - Wenli Chen (IEEE Journal on selected areas in communications)
We present a protocol for managing mobile wireless ad hoc networks. The protocol uses hierarchical clustering of nodes to reduce the number of messages exchanged between the manager and the agents (mobiles). Clustering also enables the network to keep track of mobiles as they roam. The ad hoc network management protocol (ANMP) is fully compatible with simple management protocol, version 3 (SNMPv3) and uses the same protocol data units (PDUs) for data collection. The protocol also implements sophisticated security mechanisms that can be fine-tuned to meet specific requirements. Finally, we have implemented the protocol along with a graphical user interface that allows a manager to change the view or specify management parameters on the fly